(untitled) (Bangladesh Agronomy Journal, 2019)
A field experiment was carried out at Sonapur of Muradnagar upazilla in Cumilla district under the Debidwar MLT (Multi-Location Testing) site during the rabi season of 2013-15. The experiment was conducted in the Old Meghna Estuarine Floodplain (AEZ-19) soil. The experiment was laid out in randomized complete block design (RCBD) with 3 replications.The treatments were: T1= Soil Test Based (STB) Fertilizer dose (FRG 2012), T2= T1+ 15% STB, T3= T1+ 30% STB, T4= 80% STB from inorganic fertilizer + 20% STB from CD/PM, T5= Farmers’ Practice andT6= Control. Among the treatments, T4 gave the maximum seed yield (1385.56 kg ha-1) which was at par with T1, T3 and T2 treatments. The lowest seed yield (450.20 kg ha-1) was obtained from T6 (Control). Bangladesh Agron. J. 2018, 21(2): 67-71